Protein Structural Ensembles Visualized by Solvent Paramagnetic Relaxation Enhancement. (19th December 2016) - Gong, Zhou; Gu, Xin‐Hua; Guo, Da‐Chuan; Wang, Jin; Tang, Chun
Abstract: A protein can be in different conformations when fulfilling its function. Yet depiction of protein structural ensembles remains difficult. Here we show that the accurate measurement of solvent paramagnetic relaxation enhancement (sPRE) in the presence of an inert paramagnetic cosolute allows the assessment of protein dynamics. Demonstrated with two multi‐domain proteins, we present a method to characterize protein microsecond–millisecond dynamics based on the analysis of the sPRE. Provided with the known structures of a protein, our method uncovers an ensemble of structures that fully accounts for the observed sPRE. In conjunction with molecular dynamics simulations, our method can identify protein alternative conformation that has only been theorized before. Together, our method expands the application of sPRE beyond structural characterization of rigid proteins and complements the established PRE NMR technique.